Interlegality in the Space of Sharia: Rethinking Islamic Family Law in Aceh, Indonesia - Mokhammad Samson Fajar; Abdul Qodir Zaelani; Ahmad Rajafi (Alhurriyah, 2026)
This article examines how Islamic family law governance operates within a plural legal system in Aceh, Indonesia, and questions the adequacy of conventional legal pluralism in explaining such practices. While previous studies have recognized the coexistence of state law, Islamic law, and custom, they often remain descriptive and overlook the dynamic interaction between these systems. This study offers a novel contribution by developing the concept of interlegal governance to explain how legal norms intersect and are negotiated in practice, particularly in relation to vulnerable groups. Using a qualitative socio-legal approach based on structured literature synthesis (1994–2025), this article analyzes how legal actors navigate multiple legal forums in resolving family disputes. The findings identify four interlegal patterns: normative harmonization, selective incorporation, jurisdictional bifurcation, and forum navigation. These patterns demonstrate that Islamic family law in Aceh is not governed by a single authority but through dynamic interaction among legal systems. Importantly, the study reveals that interlegality is normatively ambivalent—it can expand access to justice while also reproducing inequalities, particularly affecting women and children. This article argues that understanding Islamic law in plural societies requires moving beyond legal pluralism toward an interlegal perspective that captures both interactions and its implications for justice.